The seaside library [large type] - Novak, Brenda (Thorndike Press large print dynamic drama., 2023)
"There are secrets that bring friends together, and others that drive them apart... Mariners Island is barely ten miles long, but when Ivy, Ariana and Cam were teenagers, it was their whole world. Beyond the pristine beaches and iconic lighthouse lies the beautiful old library that belongs to Ivy's family. While that bound Ivy to the island as an adult, Ariana could not leave Mariners behind fast enough. The town holds too many...memories. Not only her unrequited feelings for Cam, but the tragedy that left a scar on the community. When a young girl went missing, a teenage Cam was unthinkably the prime suspect. Ariana and Ivy knew he couldn't have hurt anyone, and they promised to protect him--even if it meant lying on his behalf. Now, twenty years later, Ariana returns to Mariners just as new evidence emerges on the case, calling into question everything the three friends thought they knew--and everyone they thought they could trust. What really happened that night? Over the course of one eventful summer, Ariana, Ivy and Cam will learn the truth--about their pasts, their futures and the ties that still bind them as closely as the pages of a book" --